Implementasi Pelatihan Penguatan Penggerak Moderasi Beragama Aparatur Sipil Negara Kementerian Agama Di Propinsi Jawa Timur - Agus Akhmadi; Zainul Arief (Inovasi-Jurnal Diklat Keagamaan, 2022)
The training for strengthening religious moderation will be held by the Surabaya Religious Education and Training Center in 2022. This study aims to evaluate the implementation of training for strengthening religious moderation for the Ministry of Religion's State Civil Apparatus (ASN) and the religious moderation attitudes of the trainees. This research method is a qualitative descriptive of the implementation of training and the attitude of religious moderation that drives religious moderation. The research respondents were 135 people consisting of teachers, madrasa heads, extension workers, and penghulu. Data collection was carried out by means of a questionnaire. The research instrument was in the form of a religious moderation attitude scale questionnaire which was sent via google form uploads to respondents. Data processing was carried out by descriptive statistics. The results of the study indicate that the implementation of training on strengthening the driving force of religious moderation is quite satisfactory. The participants' religious moderation attitude was included in the high category.